A Pragmatic Study of Speech Acts in the Novel Rantau Satu Muara and Its Relevance to Indonesian Language Learning - Supriadi; A.Asnawi; Juliana Rahman (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study aims to describe speech acts in the novel Rantau Satu Muara by Ahmad Fuadi through a pragmatic approach and to explain their relevance to Indonesian language learning at SMP Muhammadiyah Bulukumba. This research employed a qualitative descriptive method with content analysis as the main approach. The data were taken from dialogues and utterances in the novel that contain locutionary, illocutionary, and perlocutionary acts. Data collection was conducted through reading and note-taking techniques, while data analysis was carried out by identifying, classifying, interpreting, and describing the forms and functions of speech acts found in the novel. The findings show that the novel contains various forms of speech acts, including locutionary acts, illocutionary acts, and perlocutionary acts, which reflect communication intentions, social interaction, and character responses. These speech acts also contain educational values that can support students’ language awareness, character formation, and understanding of literary texts. The study concludes that Rantau Satu Muara is relevant as an alternative teaching material in Indonesian language learning, especially in learning activities related to analyzing language use, dialogue, character values, and literary meaning in junior high school. This relevance can help students improve pragmatic competence and appreciate literary works more critically and contextually.